(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The standard treatment involves the use of first line antitubercular therapy for treating pulmonary tuberculosis (TB) in treating pulmonary tuberculosis (TB). This treatment is associated with many drug-related problems (DRPs) and adverse drug reactions (ADRs). A single blind randomized, controlled study was conducted on 250 patients to identify and evaluate the DRPs and ADRs among the newly diagnosed pulmonary TB patients in a tertiary care hospital. The patients were classified as the usual care group (Control) and pharmaceutical care intervention group (Test). At the end of follow up of the study, the DRPs were assessed by using PCNE classification V9.1. The causality assessment of ADRs was done with Naranjo algorithm, severity assessment was carried with modified Hartwig and Siegel scale and the preventability of ADRs was assessed with modified Schumock and Thornton scale. The statistical percentage analysis was done using with Microsoft Excel 2019. Of 250 participants, 88% had DRPs and developed one or more ADRs. The DRPs of Adverse drug event (possibly) occurring, unclear problem/complaint, duration of treatment too long, medication reconciliation problem and inappropriate timing or dosing intervals were found to be more. The severity of ADRs around 94.55% were mild and 5.45% were moderate. The causality of ADRs around 94.09% were possible and 5.92% were probable, while the preventability of ADRs found around 89.55% definitely preventable and 10.45% were probably preventable. The study concludes the importance of clinical pharmacists in pharmaceutical patient care will contribute in understanding different DRPs and ADRs in the management of TB.